Awareness on cervical cancer and screening practice among married women in selected wards of Pokhara Metropolitan city - Baral, Sunita; Thapaliya, Rekha; Sharma, Pushpa (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Cervical cancer is a major public health issue in low and middle income countries like Nepal. Despite being preventable and treatable, high incidence and mortality persist due to low awareness and screening. This study aimed to assess awareness and screening practices related to cervical cancer.Methods: A descriptive cross-sectional study was conducted among 257 married women aged 30 to 60 years in Pokhara Metropolitan City using simple random sampling. Data were collected through structured face to face interviews, entered into Epi Data version 3.1, and analyzed using SPSS version 16.0. Descriptive and inferential statistics, chi square test and Pearson’s correlation coefficient were applied for analysis.Results: Among respondents, 142(55.25%) were aged 30–40 years, 123(50.20%) had secondary education, and 105(40.86%) were homemakers. Marriage between ages 15 to 19 years was reported by 140(54.47%). Adequate awareness of cervical cancer was found in 122(47.47%), and 106(41.25%) had undergone screening. Awareness was significantly associated with age, ethnicity, husband’s education, and duration of marriage. Screening practice was significantly associated with age, ethnicity, income, age at marriage, duration of marriage, and menstruation status. A weak positive correlation was observed between awareness and screening practice.Conclusions: Over half of the married women exhibited inadequate awareness and low screening uptake. Enhancing cervical cancer education and promoting screening uptake is recommended.